Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations. (15th June 2023) - Shih, Pei-Chun; Chen, Hsin-Pao; Hsu, Ching-Cheng; Lin, Chung-Hsien; Ko, Chou-Yuan; Hsueh, Chao-Wen; Huang, Cheng-Yi; Chu, Tian-Huei; Wu, Cheng-Chun; Ho, Yu-Cheng; Nguyen, Ngoc Uyen Nhi; Huang, Shih-Chung; et al.
Abstract: Plasticizers are considered as environmental pollution released from medical devices and increased potential oncogenic risks in clinical therapy. Our previous studies have shown that long-term exposure to di-ethylhexyl phthalate (DEHP)/mono-ethylhexyl phthalate (MEHP) promotes chemotherapeutic drug resistance in colorectal cancer. In this study, we investigated the alteration of glycosylation in colorectal cancer following long-term plasticizers exposure. First, we determined the profiles of cell surface N -glycomes by using mass spectrometry and found out the alterations of α2, 8-linkages glycans. Next, we analyzed the correlation between serum DEHP/MEHP levels and ST8SIA6 expression from matched tissues in total 110 colorectal cancer patients. Moreover, clinical specimens and TCGA database were used to analyze the expression of ST8SIA6 in advanced stage of cancer. Finally, we showed that ST8SIA6 regulated stemness in vitro and in vivo . Our results revealed long-term DEHP/MEHP exposure significantly caused cancer patients with poorer survival outcome and attenuated the expression of ST8SIA6 in cancer cells and tissue samples. As expected, silencing of ST8SIA6 promoted cancer stemness and tumorigenicity by upregulating stemness-associated proteins. In addition, the cell viability assay showed enhanced drug resistance in ST8SIA6 silencing cells treated with irinotecan. Besides, ST8SIA6 was downregulated in the advanced stage and positively correlated with tumor recurrence in colorectal cancer. Our results imply that ST8SIA6 potentially plays an important role in oncogenic effects with long-term phthalates exposure. Graphical abstract: Image 1 Highlights: Long-term plasticizers exposure caused tumorigenesis with aberrant glycosylation. Serum levels of plasticizers are correlation with patient survival outcome. ST8SIA6 silencing promoted cancer stemness and chemotherapeutic resistance.